The Development of Student Academic Administration Services in Higher Education - Fathurrochman, Irwan; Hariani, Densi; kubuwono, Hameng; Arsil,; Amin, Muhammad; Ristianti, Dina Hajja (International Journal of Psychosocial Rehabilitation, 2020)
This Qualitative research is motivated by student satisfaction with academic services. Seeing the facts in the field shows that academic services in Student Academic Administration at State Islamic Institute of Religion Curup, the level of quality of academic services in the Academic Administration of Student Affairs State Islamic Institute of Religion Curup based on aspects of tangibles, Responsiveness, Assurance aspects of reliability and Empathy aspects. The results of this study indicate that the quality of services based on physical evidence (tangible) in this case is related to the facilities and infrastructure of service rooms and employee performance is not optimal, the quality of service based on responsiveness in terms of responsiveness to responding to students is quite good, the quality of service is based assurance (assurance) in terms of ability and friendliness of employees is quite good, the quality of service based on reliability (reliability) in terms of services that are immediately accurate and satisfying is good and the quality of service based on empathy (empathy) in terms of attention and communication between employees and students is not optimal.